Neuroprotective Effects of Oligosaccharides From Periplaneta Americana on Parkinson’s Disease Models In Vitro and In Vivo - Liu, Miao-Miao; Zhou, Nan; Jiang, Na; Lu, Kai-Min; Wu, Chuan-Fang; Bao, Jin-Ku (Frontiers in Pharmacology, 2022)
Parkinson's disease (PD) is one of the neurodegenerative diseases that characterized by obvious motor symptoms and some non-motor symptoms. Various therapeutic failed in the effective treatment of PD due to impaired neurological function in brain and various complications. Periplaneta Americana oligosaccharides (OPA), the main active ingredients extracted from the medicine residues of Periplaneta Americana (P. Americana), have been reported to exert anti-inflammatory effects. The purpose of this study was to evaluate the possible mechanisms of OPA against 1-methyl-4-phenylpyridinium (MPP+)-induced apotosis in SH-SY5Y cells and its potential neuroprotective effects in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD subacute model mice. The data demonstrated that OPA significantly reversed the MPP+-induced decrease in SH-SY5Y cell viability, decreased the percentage of apoptotic cells in a dose-dependent manner and protected SH-SY5Y cells from apoptosis by regulating the expression of apoptosis-related genes. Furthermore, OPA also alleviated the motor dysfunction of PD model mice, prevented the loss of Tyrosine hydroxylase (TH) positive cells, suppressed the apoptosis of substantia nigra cells, and improved the dysbiosis of gut microbiota in vivo, suggesting OPA had a significantly neuroprotective effect on PD model mice. These results indicated that OPA might be the candidate of complementary and alternative medicines of PD therapeutics with low-cost and high safety.